Nilai Diagnosis N-Terminal Prohormone Brain Natriuretic Peptide untuk Mendeteksi Gagal Jantung Kronik Diastolik pada Pasien Hemodialistis Rutin di Unit Hemodialistis RSUPN Dr. Cipto Mangunkusumo Jakarta - Todung Silalahi; Marulam M. Panggabean; Idrus Alwi; Suzanna I; Dharmeizar . (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2012)
Abstract Aims: to compare Ntpro-BNP levels in chronic kidney failure undergoing routine hemodialysis without diastolik heart failure,with chornic kidney failure patients undergoing routine hemodialysis with chronic diastolik heart failure Methods and results: 60 chronic kindey disease in Cipto Mangunkusumo Hospital Hemodialysis unit were undergoing routine hemodialysis between june 2007 to October 2007 were chosen for the research. Their left ventricular functions, both sys tolic dan diastolik, were measured using echocardiography. Their mean NT pro-BNP values were also recorded. Mean of NT pro –BNP in normal LV fucition without diastolik dysfuncition in 41 pepople is 11.600,2 (sta ndard deviation 10.356,1),with minimum value of 61o,8 pg/ml and maximal vaule of 35,000 pg/ml, NT pro –BNP vaue of19.170 pg/dl as diagnostic test for diastolik heart failure thus shows that it haws 84% sensitivity and 80% specificity value. Conclusion: NT pro-BNP can be used to datect chronic diastolik heart fa in patient undergoing routine hemodialysis key words: Echocardiography, NT pro-BNP, left ventricular funcition, chronic kidney failure, chronic diastolik heart failure